The Role of Social Media Use in Peer Bullying Victimization and Onset of Anxiety Among Indonesian Elementary School Children - Kaloeti, Dian Veronika Sakti; Manalu, Rouli; Kristiana, Ika Febrian; Bidzan, Mariola (Frontiers in Psychology, 2021)
Objectives: This study explored a multidimensional model of the relationships between social media use, gender, peer bullying victimization experiences, and the onset of anxiety symptoms among children. We hypothesized that greater experience of bullying would be associated with greater onset of anxiety. We also expected that gender and social media use (specifically Instagram and YouTube) would be linked with anxiety among elementary school children. To test this hypothesis, a structural equation modeling approach was used. Methods: A total of 456 elementary children aged 11–13 years from nine schools were recruited for this research. We used two psychological measures: The Screen for Child Anxiety Related Emotional Disorders (SCARED) and the Personal Experience Checklist (PECK) as well as a sociodemographic questionnaire (general demographic information and social media-related information). Results: The social media usage survey found that all participants (100%) used social media. Instagram (52.42%) and YouTube (47.58%) were the platforms most used by the participants. The Structural Equation Model results suggest that bullying victimization and gender predicted the onset of anxiety in elementary school children. The model explained 32.1% of the variance of the outcome with very adequate fit indicators based on most indices, χ2 = 173.56, df = 52, p < 0.001; CFI = 0.92; TLI = 0.94; RMSEA = 0.07 (90% CI: 0.06–0.08). Instagram use was correlated positively with generalized anxiety disorder. Gender was negatively correlated with Instagram use and positively correlated with YouTube use. Girls were found to use Instagram more and boys were found to use YouTube more. It was also found that girls had higher scores onSCARED dimensions, except for school avoidance. Girls were more prone to onset of anxiety than boys, except for school avoidance, which was not related to gender. Boys were found to experience significantly more physical bullying than girls. On the other hand, girls were found to experience more panic disorder, generalized anxiety disorder, separation anxiety disorder, and social anxiety than boys. Conclusion: This study found that bullying victimization significantly influences the onset of anxiety in children. Particular attention should be paid to cyberbullying in this context. This study also found a link between gender and anxiety—girls had a greater tendency to experience the onset of various types of anxiety, including panic disorder, generalized anxiety disorder, separation anxiety disorder, and social anxiety. Gender was also correlated with the form of bullying victimization. The findings of this study suggest that boys were more likely to experience physical bullying than girls. Interestingly, we found that Instagram use was significantly correlated with developing separation anxiety. In particular, children demonstrated school avoidance when experiencing cyberbullying. Limitations and future directions are discussed.